The approximate solutions to source inverse problem of 1-D convection–diffusion equation by LS-SVM. Issue 5 (4th May 2018) - Yu, Jiaju; Li, Fule; Yu, Shuanghe; Wu, Ziku
Abstract: This article deals with the determination of the source in 1-D convection–diffusion problem. A method which based on the least squares support vector machines is proposed. The approximate solutions consist of two parts. The first part is a known function that satisfies the initial/boundary conditions. The other part is the combination of Gauss Kernel functions with regression coefficients, which is not affected from the initial/boundary conditions. According to the principle of least squares support vector machines regression, the problem can be transformed into a quadratic programming. The method has been tested on four examples and has yielded accurate results.